Synthesis of (-)-drimenol as potential antifungal agent and synthesis of chiral substituted polyvinylpyrrolidones - Edouarzin, Edruce (Kansas State University, 2022)
The success of modern medicine to cure and treat ailments is contributed to the ability to properly diagnose the cause of the symptoms. Fungal diseases are underestimated and often disregarded as a potential public health risk. The misdiagnosis of ailments either caused or exacerbated by fungal pathogens can endanger many lives. Fungal strains such as C. auris and C. haemulonii exhibit resistance to many commonly used fungicides, suggesting a need for alternative means of treatment. (-)-Drimenol has been found to work well at inhibiting the growth of C. albicans at concentrations as low as 8 μg/ml and tolerable by Caenorhabditis elegans (roundworms) at 100 μg/ml. In this thesis I discuss the inspiration and synthesis of drimenol and analyze its potential as an antifungal agent. Catalysis is the backbone of many industrial processes and reactions. Asymmetric oxidations have been explored but there are still many shortcomings in terms of enantioselectivity. Poly‑N‑vinylpyrrolidinone (PVP) is an efficient stabilizer for nanoclusters and has been found to regulate aggregation of the metal atoms. Some researchers have reported increased reactivity by these supported clusters, but enantioselective oxidations were still a challenge. The Hua lab previously reported their success in performing stereo- and regioselective oxidations on various alkenes and cyclic alkanes using C5-substituted PVPs stabilized Pd/Au and Cu/Au bimetallic nanoclusters, respectively. In this thesis, I describe the synthesis of a second generation C3-substituted PVP to determine how the alternate substitution may affect the enantioselectivity.
Keywords: Drimenol; Chiral-substituted polyvinylpyrrolidone; Synthesis; Polymer